Incidence, Risk Factors, and Treatment Outcome of Acute Renal Allograft Rejection - Remyasri Akhil; Eby Mathew; Bipi Prasannan; Vishnu Dev Urs; V. Narayanan Unni (Indian Journal of Transplantation)
Background: Acute rejection occurs at any time following renal transplantation. The study aims to find the incidence, risk factors, and outcome of acute rejection in kidney transplantation. Materials and Methods: Retrospective cohort study conducted from January 2015 to April 2023, included patients with biopsy-proven acute graft rejection. Data were collected from electronic medical records. Rejection and no rejection groups were compared for the variables. Results: Out of 371 patients, acute rejection occurred in 36 (9.7%) patients at 1 year of transplantation. Thirty (8%) were early acute rejections (EARs) and 22 (6%) were late acute rejections (LARs). Higher human leukocyte antigen (HLA) mismatches, historical positive crossmatch, and history of blood transfusions were risk factors for acute rejection (P < 0.05). Incidence of LAR beyond 1 year was 11/23 (48%) in those who had received induction therapy at transplantation versus 5/29 (17.2%) in those who did not (P = 0.045). One out of five patients (3.4%) who received antithymocyte globulin (ATG) experienced EAR, in contrast to 8/18 (5.2%) patients who received basiliximab (P = 0.037). A complete response to treatment was observed in 22/30 (73.3%) patients with EAR and 2/22 (9.09%) with LAR (P < 0.001). At 23.77 ± 24.6 months of follow-up, graft survival was 12/12 (100%) in those with early T-cell-mediated rejection (TCMR) compared to 5/9 (55.6%) with late acute TCMR (P = 0.01). Conclusion: The incidence of acute rejection was highest within the first posttransplant year. Higher HLA mismatches, historical positive crossmatch, and history of blood transfusion were risk factors for acute rejection. ATG was effective in preventing EAR. LAR occurring beyond the first posttransplant year was independent of induction therapy at time of transplantation. Treatment response was better with EAR compared to LAR. Graft survival was better with early acute TCMR compared to late acute TCMR.